2015
DOI: 10.1017/s0022377815001221
|View full text |Cite
|
Sign up to set email alerts
|

A 3-D MHD equilibrium description of nonlinearly saturated ideal external kink/peeling structures in tokamaks

Abstract: Novel free boundary magnetohydrodynamic equilibrium states with spontaneous three-dimensional (3-D) deformations of the plasma-vacuum interface are computed. The structures obtained look like saturated ideal external kink/peeling modes. Large edge pressure gradients yield toroidal mode number n = 1 distortions when the edge bootstrap current is large and higher n corrugations when this current is small. Linear ideal MHD stability analyses confirm the nonlinear saturated ideal kink equilibrium states produced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…In addition we point out that in the tanh model, contrarily to the step case, the shape of the eigenfunctions depends on the value of δq (and so on the corresponding growth rate). We note that the radial structure of the main and sidebands harmonics closely resembles what has been found numerically in three-dimensional equilibria simulations (Cooper et al 2015(Cooper et al , 2016a and in MHD stability calculations (Medvedev et al 2006;Zheng et al 2013a,b). We shall now consider the case with a resistive wall.…”
Section: Analysis Of the Dispersion Relation Of The Tanh Modelsupporting
confidence: 83%
See 2 more Smart Citations
“…In addition we point out that in the tanh model, contrarily to the step case, the shape of the eigenfunctions depends on the value of δq (and so on the corresponding growth rate). We note that the radial structure of the main and sidebands harmonics closely resembles what has been found numerically in three-dimensional equilibria simulations (Cooper et al 2015(Cooper et al , 2016a and in MHD stability calculations (Medvedev et al 2006;Zheng et al 2013a,b). We shall now consider the case with a resistive wall.…”
Section: Analysis Of the Dispersion Relation Of The Tanh Modelsupporting
confidence: 83%
“…We note that the radial structure of the main and sidebands harmonics closely resembles what has been found numerically in three-dimensional equilibria simulations (Cooper et al. 2015, 2016 a , b ) and in MHD stability calculations (Medvedev et al. 2006; Zheng et al.…”
Section: Analysis Of the Dispersion Relation Of The Tanh Modelsupporting
confidence: 82%
See 1 more Smart Citation
“…Equation ( 14) is evaluated by means of ( 6) and ( 7) while ( 15) is obtained from (4) (see [28]). Evaluating (10) at r * and a gives respectively X ± (r * ) = r ±m * L ± /(2 ± m + C ± ) and X ± (a) = a ±m L ± /(2 ± m + B ± ) having used (12). Integration of equation (10) from r * to a finally gives ) , where β = 2p * q 2 /B 2 0 , ε p = r p /R 0 and [23]:…”
Section: Pedestal Low-shear Regionmentioning
confidence: 99%
“…Three dimensional free boundary Analytic stability criteria for edge MHD oscillations in high performance ELM free tokamak regimes D. Brunetti 1 , J.P. Graves 2 , E. Lazzaro 1 , A. Mariani 2,a , S. Nowak 1 , W.A. Cooper 2 and C. Wahlberg 3 MHD equilibria simulations of JET and TCV-like plasmas with large edge bootstrap current exhibit a distorted boundary with a dominant n = 1 Fourier component driven mainly by non axisymmetric contributions to the parallel current density [12][13][14]. Nonlinear simulations of QH-mode DIII-D plasma discharges showed that medium-n (∼3, 4, 5) harmonics are linearly the most unstable modes but the nonlinear phase is dominated by saturated stationary low-n modes [15].…”
Section: Introductionmentioning
confidence: 99%